Lady Jane [videorecording (DVD)] - Nunn, Trevor; Bonham Carter, Helena, 1966-; Elwes, Cary, 1962-; Wood, John, 1930-2011; Hordern, Michael, 1911-1995 (Widescreen DVD collection, 2002)
"In 1553, England's idle rich were anything but idle. With the blessing of the royal family, they plundered the riches of the church, stole the finest farmlands, and generally took all the best things the country had to offer. A cousin to the infamous Henry VIII, Lady Jane Grey disapproved of the way her fellow nobles behaved, and disagreed with their religious beliefs. But as a sheltered 16-year-old, there wasn't much she could do about it. Then, through a strange turn of events, Lady Jane Grey was crowned Queen Jane, ruler of all England. Based on the true story of the girl who found herself Queen of England for nine days at age 16"--Container.